ANALISIS DESKRIPTIF KEPEMIMPINAN BIDANG BINA PENDIDIKAN DASAR (DIKDAS) DI DINAS PENDIDIKAN BALANGAN - Setiawan , Irza (PPPM STIA Amuntai, 2019)
A leader must have a good competence to successfully bring the organization for its intended purpose. If a led organization is engaged in education field, of course a leader must also have a competence that qualified both skill, science, and experience in the field of education. However, related to that, it also found some problems about leadership, namely the leader is less exemplary discipline, less competent in the field, less provide guidance, less coordination and unable to make their own decisions. Based on the above things, this study aims to find out how the leadership in the field of basic education (DIKDAS) is, what factors affect the leadership in the field of basic education (DIKDAS), and what effort are being made to improve the leadership in the field of basic education (DIKDAS) at Dinas Pendidikan Balangan district. The location of research is at the office of Dinas Pendidikan Balangan district. The approach used is a qualitative approach with a qualitative description type. Data collection technique used are interviews, observation, and documentation. The source of data is amounted to 14 people. After the data collected, then analyzed through 3 stages, namely data editing, data presentation, and verification or drawing conclusion. The result of the research indicate that the leadership in the field of basic education (DIKDAS) has not been entirely good. This can be seen from the side of responsibility that is less independent as a leader and does not have the desire to excel. On the other hand, the leader in the field of basic education (DIKDAS) is considered to have capacity in the from of intelligence, speech and judgment ability. From the aspect of achievement is an appropriate bachelor degree and a quite estensive knowledge. From the aspect of responsibility is a quite good initiative, diligent, tenacious, and confident. From the aspect of participation, that is active, have high sociability, cooperative, and able to adjust. The factors that influence leadership are the expertise and employee loyalty to leader, education and training experience, and the leader’s intelligence. Then, the effort to improve the leadership is delegation of tasks to subordinates, the approach by the leadership to subordinates and training as well as discussion. The suggestions to improve the leadership in the field of basic education (DIKDAS) are the leaders need to be a motivator for subordinates, have the attitude of independence, one of them is able to make their own decisions that precarious, and have the desire to excel in order to spur achievement.